Neuromuscular responses to incremental caffeine doses: performance and side effects - Pallarés, Jesús G; Fernández-Elías, Valentín E; Ortega, Juan F; Muñoz, Gloria; Muñoz-Guerra, Jesús; Mora-Rodríguez, Ricardo (Medicine and science in sports and exercise, 2013)
The purpose of this study was to determine the oral dose of caffeine needed to increase muscle force and power output during all-out single multijoint movements. Thirteen resistance-trained men underwent a battery of muscle strength and power tests in a randomized, double-blind, crossover design, under four different conditions: (a) placebo ingestion (PLAC) or with caffeine ingestion at doses of (b) 3 mg · kg(-1) body weight (CAFF 3mg), (c) 6 mg · kg(-1) (CAFF 6mg), and (d) 9 mg · kg(-1) (CAFF 9mg). The muscle strength and power tests consisted in the measurement of bar displacement velocity and muscle power output during free-weight full-squat (SQ) and bench press (BP) exercises against four incremental loads (25%, 50%, 75%, and 90% one-repetition maximum [1RM]). Cycling peak power output was measured using a 4-s inertial load test. Caffeine side effects were evaluated at the end of each trial and 24 h later. Mean propulsive velocity at light loads (25%-50% 1RM) increased significantly above PLAC for all caffeine doses (5.4%-8.5%, P = 0.039-0.003). At the medium load (75% 1RM), CAFF 3mg did not improve SQ or BP muscle power or BP velocity. CAFF 9mg was needed to enhance BP velocity and SQ power at the heaviest load (90% 1RM) and cycling peak power output (6.8%-11.7%, P = 0.03-0.05). The CAFF 9mg trial drastically increased the frequency of the adverse side effects (15%-62%). The ergogenic dose of caffeine required to enhance neuromuscular performance during a single all-out contraction depends on the magnitude of load used. A dose of 3 mg · kg(-1) is enough to improve high-velocity muscle actions against low loads, whereas a higher caffeine dose (9 mg · kg(-1)) is necessary against high loads, despite the appearance of adverse side effects.